Impact of Summer Air Temperature on Water and Solute Transport on a Permafrost‐Affected Slope in West Greenland - Zastruzny, Sebastian F.; Sjöberg, Ylva; Jensen, Karsten H.; Liu, Yijing; Elberling, Bo (Water resources research, 2024)
In Arctic landscapes, the active layer forms a near‐surface aquifer on top of the permafrost where water and nutrients are available for plants or subject to downslope transport. Warmer summer air temperatures can increase the thickness of the active layer and alter the partitioning of water into evapotranspiration and discharge by increasing the potential evapotranspiration, the depth to the water table, and changing the flow paths but the interacting processes are poorly understood. In this study, a numerical model for surface‐ and subsurface cryo‐hydrology is calibrated based on field observations from a discontinue permafrost area in West Greenland considered sensitive to future climate changes. The validated model is used to simulate the effect of three summers with contrasting temperature regimes to quantify the variations in the active layer thickness, the resulting changes in the water balance, and the implications on solute transport. We find that an increase of summer air temperature by1.6°C, under similar precipitation can increase the active layer thickness by 0.25 m, increase evapotranspiration by 5%, and reduce the total discharge compared to a colder summer by 9%. Differences in soil moisture and evapotranspiration between upslope and downslope were amplified in a warm summer. These hydrological differences impact solute transport which is 1.6 times faster in a cold summer. Surprisingly, we note that future warmer summer with increase in permafrost thaw may not necessary lead to an increase in discharge along a hill slope with underlying permafrost. Plain Language Summary Precipitation that falls in the Arctic can be restricted from moving deeper into the subsurface by the permanently frozen soil that constraints water movement close to the surface in a layer that thaws every year during the summer. Warmer summers make this layer thaw deeper and water moves to deeper soil. In the deeper soil water moves more slowly as the material is more difficult to flow through, and thus also solute move slower. Moreover, the amount of water that returns to the atmosphere becomes higher with warmer temperatures. We measure soil conditions, and the velocity of solutes in the field along a hillslope in Greenland. Based on warm, average and cold years, we build a model capable of simulating storage and movement of water and the temperature in the soil. We use the model to test a warm, a normal, and a cold summer, and analyze the effects on the amount of water that reaches the end of the hillslope. We show that less water will move across the slope in warmer summers, but solutes travel at a higher velocity, and that cold summers have only a small effects on the movement of this solute. Key Points Warmer summers reduce discharge from hillslope by 35% Solute movement is non‐uniform and controlled by precipitation events Warmer summers amplify differences between up‐ and downslope